2018
DOI: 10.1111/febs.14385
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Hog1 MAPK by the Ssk2/Ssk22 MAP3Ks, in the absence of the osmosensors, is not sufficient to trigger osmostress adaptation in Saccharomyces cerevisiae

Abstract: Yeast cells respond to hyperosmotic stress by activating the high-osmolarity glycerol (HOG) pathway, which consists of two branches, Hkr1/Msb2-Sho1 and Sln1, which trigger phosphorylation and nuclear internalization of the Hog1 mitogen-activated protein kinase. In the nucleus, Hog1 regulates gene transcription and cell cycle progression, which allows the cell to respond and adapt to hyperosmotic conditions. This study demonstrates that the uncoupling of the known sensors of both branches of the pathway at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Osmostress can activate the Hog1 MAPK in the absence of the upstream osmosensors Several studies have reported that Hog1 can be activated at very high osmolarity (> 1 M NaCl) in strains that are defective in both the SLN1 and SHO1 branches, such as ssk1D ste11D and ssk2/22D sho1D (Van Wuytswinkel et al, 2000;O'Rourke & Herskowitz, 2004;Zhi et al, 2013;Vázquez-Ibarra et al, 2019). Since each of the strains used in those studies expressed at least one MAP3K in the HOG pathway (Ssk2, Ssk22, or Ste11), the results were interpreted as evidence for an alternative mechanism for MAP3K activation following osmostress.…”
Section: Resultsmentioning
confidence: 99%
“…Osmostress can activate the Hog1 MAPK in the absence of the upstream osmosensors Several studies have reported that Hog1 can be activated at very high osmolarity (> 1 M NaCl) in strains that are defective in both the SLN1 and SHO1 branches, such as ssk1D ste11D and ssk2/22D sho1D (Van Wuytswinkel et al, 2000;O'Rourke & Herskowitz, 2004;Zhi et al, 2013;Vázquez-Ibarra et al, 2019). Since each of the strains used in those studies expressed at least one MAP3K in the HOG pathway (Ssk2, Ssk22, or Ste11), the results were interpreted as evidence for an alternative mechanism for MAP3K activation following osmostress.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 Engineering xylose metabolism in yeasts to produce Biofuel: Xylose assimilation pathway followed by Oxidative and Non-oxidative Pentose Phosphate Pathway [35] In the process of yeast xylose metabolism, xylose is transformed into xylulose through the process of isomerization, which occurs under aerobic conditions [34]. Two distinct routes -the oxidoreductase pathway and the isomerase pathway, are used by xylose-fermenting bacteria to transform xylose into xylulose [34]. However, xylose-fermenting yeasts utilize the oxidoreductase pathway, which consists of two enzymatic reactions [34].…”
Section: Modified Xylose Metabolismmentioning
confidence: 99%
“…Two distinct routes -the oxidoreductase pathway and the isomerase pathway, are used by xylose-fermenting bacteria to transform xylose into xylulose [34]. However, xylose-fermenting yeasts utilize the oxidoreductase pathway, which consists of two enzymatic reactions [34].…”
Section: Modified Xylose Metabolismmentioning
confidence: 99%
“…Some reports indicate that Hog1 may be activated by an alternative mechanism to the known sensors of the Sho1 and Sln1 branches, and that Ssk2 could be activated by an alternative route as an additional input for Hog1 phosphorylation under severe hyperosmotic stress [47,48]. However, phosphorylation of this MAPK in the absence of the known sensors of both branches fails to induce a protective response due to a diminished transcription activity of hyperosmolarity-responsive genes and defects in cell cycle regulation [49]. It is therefore tempting to speculate that one of the main roles of this alternative pathway could be to feed the CWI pathway.…”
Section: The Mkks and Mapks Of The Hog And Cwi Pathways Form A Proteimentioning
confidence: 99%